Optimizing Populations of SAI Tactile Mechanoreceptors to Enable Activities of Daily Living - Rivest, Isabelle I. (2011)
At present, the dense network of peripheral afferents between finger and brain and the large size of engineered sensors preclude the recreation of biologically observed afferent populations. This work uses a validated computational model of cutaneous skin and tactile afferents to evaluate sparse populations in performing tasks required in activities of daily living. Using a model (3D finite element representation of fingertip skin, linear bi-phasic transduction function, and leaky-integrate-and-fire neuronal model), we systematically varied populations of tactile receptors in dimensions of density (100, 45, 20, and 10 sensors/cm(2)) and size (diameter 0.1, 0.2, 0.5, and 1.0 mm) to determine if a given modeled population can discriminate spheres and cylinders representative of objects used in activities of daily living. Using a scoring system which allows for direct comparisons between the populations, our results indicate that a population must have at least 20 sensors per cm(2) to maintain response resolution in these activities of daily living and that larger-sized sensors do not degrade response resolution.